(untitled) (American Journal of Islam and Society, 2009)
Emerging from the heap of the Soviet empire into a backwater landmass, the CentralAsian republics of Kazakhstan, Kyrgystan, Tajikistan, Turkmenistan, and Uzbekistan have been increasingly gaining in significance and importance as the rumblings of a new Great Game is being sounded on their territory.According to this book, the three great powers – the United States, Russia, and China – are expected to play determinate roles in the politics and shaping of this region’s evolution on the world stage. The role of these newly independent republics, however, is less clear or easy to forecast, however, for they seem to be still in the process of forging their national identities and deciding upon the thrust of their global relations, alliances, and interests. In addition, whether they will continue to be able to maintain their newly gained independence, particularly given their vulnerability as landlocked countries, remains a significant question. Russia, their earlier master, is seeking to reassert its position in what it considers to be its natural sphere of influence. The rising neighboring Chinese giant is developing both economic and strategic interests beyond its borders and into that region. The American superpower is intruding as a major player into both countries’ backyard under the pretext of fighting terrorism and spreading freedom and democracy (p. 2). The outcome of the interplay of sometimes traversing yet frequently conflicting geopolitical as well as economic interests is what this book seeks to explore. Fusing the explosive elements of geopolitics, religion, and energy, this four-part book brings together twenty international policy and security analysts in a conversation about the meaning, from different perspectives, of a post-9/11 world to the United States and its allies (actual or potential), Russia, and China, as well as to regional powers and the CentralAsian republics ...